Baba Jukwa’s Facebook page: A possible counter hegemonic space for political transformation in Zimbabwe - Mutetwa, Stanley (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
This study focuses on how the Baba Jukwa Facebook page has been appropriated as a potential counter hegemonic space for the circulation of public opinion during the run up till post 2013 harmonised elections in Zimbabwe. This current study wishes to explore the role played by social media in Zimbabwe in the run up to the 2013 election especially on Facebook through participation on the Baba Jukwa page. Focus will be on the nature of the discourses in the posts and how the participants on the page engaged in debates around these posts. I will also interrogate how the discourses in the posts on the Baba Jukwa Facebook page were taken up by the main stream media and how it also clashed with dominant political discourses as enshrined in government publications and web-sites. This will shed light on the impact of the page and how it enlarged the public sphere in the country as a counter hegemonic platform.